19.6k views
0 votes
What is the answer of 10a2b + ab2 – 10ab + 3a2b + 4ab – 7ab2

User Vetrivel
by
5.2k points

2 Answers

3 votes

10a^2b + ab^2 - 10ab + 3a^2b + 4ab - 7ab^2

Combine like terms:

= 13a^2b - 6ab - 6ab^2

Take out common factor ab:

= ab(13a - 6 - 6b)
User Howlium
by
5.3k points
6 votes
combine like terms

10a-10a+3a = 3a
2b+2b + 4b
ab2-10ab+4ab-7ab2 = - 18ab

answer: 3a + 4b + 18ab
User Hcs
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.